Pengembangan Model Latihan Pola Penyerangan Permainan Bola Basket pada Ekstrakurikuler di SMAN 21 Palembang. - Oktariansyah, M. ilham; Kumbara, Hengki; Mahendra, Agung (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of a training model for attacking patterns in basketball games during extracurricular activities at SMAN 21 Palembang was the focus of this research. The exploration strategy utilized in this examination is Innovative work (R and D) from Borg and Gall. Information assortment was done utilizing a survey, an exploration test of b-ball extracurricular understudies at SMAN 21 Palembang to direct a restricted preliminary of 10 extracurricular understudies. Investigation of examination information utilizing a viable poll. The validation of the initial product's feasibility by material experts yielded this study's results, which met the criterion "Practical" with a percentage of 66%. This indicates that product development can be used. The results of the limited trial were 87.2%, and they met the criteria for "Very Practical," which means that using it is very possible. The finished product is a training model book for basketball game break attack patterns.